Impact of The Announcement of Unusual Market Activity in Indonesia Stock Exchange: Unusual Market Activity, Abnormal Return, Event Study - Widhi Astari; Gerianta Yasa (Jurnal AKSI (Akuntansi dan Sistem Informasi), 2023)
The purpose of this study is to empirically prove the information content of unusual market activity announcements by hiding how the capital market thinks before and after an announcement to the market whether the objectives of the Indonesian Stock Exchange have been achieved. This research is an event study with an observation period of 5 days. This study used a purposive sampling technique in taking samples using the one sample T-test as a method of data analysis. This study covers 2021 with 228 announcements of Unusual Market Activity, observations on the Indonesian Stock Exchange (IDX). Based on the results of the analysis, the change in abnormal returns that occurs indicates that the market has responded to this announcement mechanism. Investors responded quickly to the announcement of Unusual Market Activity. This can be seen from the decrease in abnormal returns after the announcement, which previously experienced an increase as a result of unusual price movements. The aim of the Indonesian Stock Exchange to restore new efficiency with this Unusual Market Activity announcement mechanism has been achieved. This study is the first to exclusively select a post-covid-19 year, 2021, and use the event study method. New insights into this are providing useful information for investors, academics, policy makers and other stakeholders